Enhancing Students’ Presentation Skill using Digital Media at SMAN 10 Palangka Raya - Yonatan Ari Santoso; Gabriela Elsandika; Reni Agustiani; Samsul Arifin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The purpose of this activity is to overcome the issue of tedious presentations by the students of SMAN 10 Palangka Raya. This issue occurs due to the lack of students' digital literacy, affecting their public speaking abilities. For this reason, the team provided the use of digital media mentoring to students for problem-solving. The digital media used in this activity were Prezi and Canva. The mentoring used explanation and learning-by-doing methods. The activity was held on May 2023. The students received the information well. It was proven by the questionnaires that were answered, 92.3% stated that this activity was useful to enhance the knowledge of the use of digital media in presentations. They stated that this activity could help make presentations more interesting and interactive.